2008
DOI: 10.1080/10640260802570130
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Family-Based Treatment for Adolescent Anorexia Nervosa: 18- and 36-Month Follow-ups

Abstract: The current study evaluated the outcome of family-based treatment for female adolescents with anorexia nervosa (N = 32), at the Anorexia-Bulimia Outpatient Unit in Göteborg, Sweden. Patients/parents were assessed pre-treatment, at 18- and 36-month follow-ups concerning eating disorder symptoms, general psychopathology, family climate and BMI. At the 36-month follow-up, 75% of the patients were in full remission with reduction in eating disorder symptoms and internalizing problems and they experienced a less di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
0
28
0
5
Order By: Relevance
“…It has been shown to be effective in an open trial involving 20 participants at another U.S. academic centre and the authors suggest that this is a first step in providing evidence of successful dissemination (Loeb et al, 2007). Another recent pilot study examining a combination of conjoint and separated Family-Based Treatment also has shown positive results in Sweden (Paulson-Karlsson, Engstrom, & Nevonen, 2009). However, these studies did not examine aspects of dissemination such as treatment fidelity and acceptability.…”
mentioning
confidence: 99%
“…It has been shown to be effective in an open trial involving 20 participants at another U.S. academic centre and the authors suggest that this is a first step in providing evidence of successful dissemination (Loeb et al, 2007). Another recent pilot study examining a combination of conjoint and separated Family-Based Treatment also has shown positive results in Sweden (Paulson-Karlsson, Engstrom, & Nevonen, 2009). However, these studies did not examine aspects of dissemination such as treatment fidelity and acceptability.…”
mentioning
confidence: 99%
“…Investigations into the change processes that occur over the course of structural family therapy are notably absent [7], [40]. In families of AN patients, restructuring typically involves several overlapping processes:…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the key features of these therapeutic changes still require identification and characterisation. Specifically, the critical variables involved in the mechanisms leading to the improvement of nutritional and psychological states of AN patients still need to be defined [5], [7]. As conflictual communication and nonverbal behaviour in families of patients with psychiatric disorders have been considered as fundamental components of interaction processes [8]–[10], they constitute important variables for revealing key features of therapeutic changes in family therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several methodological limitations were identified in the studies assessed: lack of description regarding the inclusion and exclusion criteria 29,30 , loss of a significant number of participants (> 25%) during treatment and follow-up 9,24 , lack of clarity regarding the remission criteria or remission assessed exclusively on the basis of biological markers 12,25,[29][30][31] , difficulty in randomizing baseline participants 26,31 , presence of confounding variables, such as the need for hospitalization, the use of antidepressants for the treatment of comorbidities, which were not necessarily controlled in the analyses 18,22,26,27,30,31 and non-probabilistic samples 20,25,29,30 . In only one study no methodological limitations were found 28 .…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…The use of proven effective treatments by the respective health care professionals, is therefore fundamental. However, due to the complex interaction of clinical and psychiatric problems, with emphasis on the ambivalent attitudes of patients and their families towards treatment 8,10 , there are significant obstacles that moderate the effectiveness of psychotherapeutic interventions and contribute to a limited number of studies in the area 11,12 .…”
Section: Introductionmentioning
confidence: 99%